2021
DOI: 10.1007/s00330-020-07623-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and chest CT features as a predictive tool for COVID-19 clinical progress: introducing a novel semi-quantitative scoring system

Abstract: Objective Proposing a scoring tool to predict COVID-19 patients' outcomes based on initially assessed clinical and CT features. Methods All patients, who were referred to a tertiary-university hospital respiratory triage (March 27-April 26, 2020), were highly clinically suggestive for COVID-19 and had undergone a chest CT scan were included. Those with positive rRT-PCR or highly clinically suspicious patients with typical chest CT scan pulmonary manifestations were considered confirmed COVID-19 for additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…We found that ICU admission, more extended hospitalization, and recovery period were associated with higher total CT scores and consolidation opacities in chest CT of these patients. Similarly, a previous study showed a higher pulmonary score ≥ of 8 accompanied by age ≥ 53, and SpO 2 ≤ 91 predicts ICU admission and mortality (27). Deepak Nagra et al also reported a higher lung opaci cation score is a reliable predictor of ICU admission for COVID-19 patients (28).…”
Section: Chest Ct Predictors Of Unfavorable Outcomesmentioning
confidence: 78%
“…We found that ICU admission, more extended hospitalization, and recovery period were associated with higher total CT scores and consolidation opacities in chest CT of these patients. Similarly, a previous study showed a higher pulmonary score ≥ of 8 accompanied by age ≥ 53, and SpO 2 ≤ 91 predicts ICU admission and mortality (27). Deepak Nagra et al also reported a higher lung opaci cation score is a reliable predictor of ICU admission for COVID-19 patients (28).…”
Section: Chest Ct Predictors Of Unfavorable Outcomesmentioning
confidence: 78%
“…Few months after the first reports of coronavirus disease 2019 (COVID- 19), it was declared a pandemic [1]. Given its high transmissibility, SARS-CoV-2 has infected millions of people worldwide and has placed a huge burden on the healthcare system [2]. Some infected patients develop acute respiratory distress syndrome (ARDS), multiple organ failure, pulmonary embolism, and heart failure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…3 There is a high variability in the reported mortality across invasively ventilated COVID-19 patients. [4][5][6] The severity of loss of aeration, typically assessed by chest computed tomography (CT) scan, has been related to outcomes in hospitalized COVID-19 patients, [7][8][9] but CT-scan capacity is limited and may not be available in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%